Development Project Evaluation Tebangi Besar–Kayu Agung Lampung Toll Road - Yekti Condro Winursito; Handoyo; Iriani; Dwi Sukma Donoriyanto; Irma Dian; Mega Cattleya Prameswari Annissaa Islami; Rizky Setiawan (Future Science)
Project management is a process of activities to manage organizational resources owned by the company to achieve certain goals. The Terbangi Besar-Kayu Agung Lampung toll road construction project is a project that must be completed in a short time. This study has a purpose to evaluate the performance of the construction project of the Terbangi Besar-Kayu Agung Lampung toll road using the PERT and CPM methods with a toll road length of 189.2 km (117.6 miles). Based on the results obtained by using these two methods, the project completion time which was originally 238 days can be completed in just 119. There are several alternative proposals. The alternative proposal by adding work shifts that have crashed 32 times has an optimal cost of IDR 39,154,229,627.03 and an optimal time of 119 days. While the alternative of increasing the capacity of the equipment produces an optimal time of 189 days and an optimal cost of IDR 39,205,747,076.44 with the crashing process reaching 12 times of crashing. The Toll Road Development Project Planning is scheduled to have a normal time to work for 238 days at a total cost of IDR 39,349,097,164.38.